2000
DOI: 10.1007/s004080000040
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Lavage: A Novel Diagnostic Approach For Diagnosing Exudative Pleural Effusion

Abstract: Patients with pleural effusions frequently present a diagnostic and therapeutic challenge. The diagnosis is based on the interpretation of the results of thoracentesis or pleural biopsy. When a malignant tumor metastasizes to the pleura, tumor cells can be seeded over the mesothelial surface or in the subserous layer. In the former situation, tumor cells are abundant in pleural fluid, but in the latter, few malignant cells are exfoliated into the pleural cavity, and microscopic deposits may not be visualized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The initial cytological results done by thoracentesis were negative. Mohamed [8] also found that the diagnostic yield of pleural lavage cytologic findings in malignant pleural effusions (84%) was greater than that of pleural fluid done by thoracentesis cytologic findings (62%).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The initial cytological results done by thoracentesis were negative. Mohamed [8] also found that the diagnostic yield of pleural lavage cytologic findings in malignant pleural effusions (84%) was greater than that of pleural fluid done by thoracentesis cytologic findings (62%).…”
Section: Discussionmentioning
confidence: 93%
“…Ali [2] also did not report any complications apart from some pain. No complication was recorded with pleural lavage procedures similar to Ali [2] and Mohamed [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Pleural lavage Pleural lavage cytology has been performed for staging in lung and esophageal cancer patients without pleural effusion. [8][9][10][11][12] Patients with a positive pleural lavage are recommended to be staged higher. [8] e fluid is aspirated after instilling physiologic saline solution into the pleural cavity prior to the resection of the tumor.…”
Section: Peritoneal Washingmentioning
confidence: 99%
“…[ 8 ] The fluid is aspirated after instilling physiologic saline solution into the pleural cavity prior to the resection of the tumor. [ 8 - 10 ] Although defined morphologic criteria are not found in the literature, the cytopathology of pleural lavages should be evaluated similarly to those of cells in peritoneal washings, including the routine preparation of cell-blocks. Intraoperative touch cytology, [ 13 ] close pleural brushings , [ 15 ] and diaphragmatic scrapes [ 14 ] have also been performed for detection of serosal involvement by cancer.…”
Section: Sampling Techniquementioning
confidence: 99%